ANALISIS FAKTOR KESULITAN BELAJAR IPAS SISWA KELAS III SD NEGERI CIPINANG CEMPEDAK 07 - Pramudita Rita Anjarwati; Adi Putra; Petrus Paulus Mbette (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning difficulties refer to an individual's inability or disturbances in the learning process or acquiring knowledge. Students experiencing learning difficulties certainly have underlying factors or reasons why they find it challenging to learn. This study aims to analyze and explain the factors contributing to students' learning difficulties in the IPAS subject for third-grade students at SD Negeri Cipinang Cempedak 07. The causes of learning difficulties among third-grade students at SD Negeri Cipinang Cempedak 07 include Social, Intellectual, and Educational Factors. The subjects of this research are third-grade students at SD Negeri Cipinang Cempedak 07. The method used is qualitative research. The results and discussion of this study indicate that the dominant factor influencing difficulties in IPAS learning in third grade at SD Negeri Cipinang Cempedak 07 is the social factor, where the learning environment at school and parental support at home significantly affect students' learning processes and outcomes. Approximately 41% of students lack focus and do not pay attention to the teacher when teaching because of an unconducive classroom atmosphere, which leads to difficulties in learning and understanding the material. Additionally, intellectual factors such as difficulty recalling previous lessons and educational factors like inadequate school facilities also need to be considered by the school, teachers, and parents as support for students in the IPAS learning process in elementary school.